Enhancing Global Health Security in Sub-Saharan Africa: The case for integrated One Health surveillance against zoonotic diseases and environmental threats - Pierre Gashema; Placide Sesonga; Patrick Gad Iradukunda; Richard Muvunyi; Jean Claude Mugisha; Jerome Ndayisenga; Tumusime Musafiri; Richard Habimana; Radjabu Bigirimana; Alice Kabanda; Misbah Gashegu; Noel Gahamanyi; et al. (One Health, 2025)
Integrated One Health surveillance is pivotal to Africa's future health security, particularly in preventing and managing zoonotic and environmental health threats. The One Health strategy recognizes the interconnectedness of human, animal, and environmental health, allowing a holistic framework for tracking and responding to emerging and re-emerging pathogens. The One Health approach facilitates cross-sectoral data sharing and enhances surveillance, enabling the early detection and response to potential outbreaks. This proactive approach shifts the paradigm from reactive crisis management to preventive containment strategies. However, challenges such as funding gaps, limited infrastructure, limited diagnostic capacity, and weak multi-sectoral and cross-border collaborations remain. This perspective paper aims to 1) explore the effectiveness of integrated One Health surveillance in early detection and response to zoonotic diseases and environmental threats in Sub-Saharan Africa (SSA), and 2) identify key challenges and proposed solutions to strengthen regional health security. A multisectoral laboratory working group (MLWG) emerged as a pillar to enable active surveillance targeting humans, animals, and the environment. This paper highlighted essential strategies for enhancing One Health surveillance in SSA in light of the recent Marburg virus disease in Rwanda. It emphasizes environmental sampling through animal excreta and wastewater surveillance for early zoonotic detection, advocates for point-of-care polymerase chain reaction (PCR) testing platforms, and multiplex models to improve decentralized diagnostics. With 48 % of African nations incorporating One Health in national agendas, a unified continental framework is needed to support broader adoption and advance regional health security.